2018
DOI: 10.1186/s41747-018-0063-4
|View full text |Cite
|
Sign up to set email alerts
|

Multicolour imaging with spectral photon-counting CT: a phantom study

Abstract: BackgroundTo evaluate the feasibility of multicolour quantitative imaging with spectral photon-counting computed tomography (SPCCT) of different mixed contrast agents.MethodsPhantoms containing eleven tubes with mixtures of varying proportions of two contrast agents (i.e. two selected from gadolinium, iodine or gold nanoparticles) were prepared so that the attenuation of each tube was about 280 HU. Scans were acquired at 120 kVp and 100 mAs using a five-bin preclinical SPCCT prototype, generating conventional,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 42 publications
2
75
0
Order By: Relevance
“…By using multiple energy thresholds, an xray photon counting spectral imaging (x-CSI) approach can be used, whereby the spectral overlap between low and high energy bins is greatly reduced, and far more energy bins can be reconstructed (up to 8 in some implementations [5]) compared with the 2 in dual energy set-ups. This allows for a range of benefits, including better material decomposition [6], soft tissue contrast, and lower flux rates to be achieved for a given image quality [7].…”
Section: Introductionmentioning
confidence: 99%
“…By using multiple energy thresholds, an xray photon counting spectral imaging (x-CSI) approach can be used, whereby the spectral overlap between low and high energy bins is greatly reduced, and far more energy bins can be reconstructed (up to 8 in some implementations [5]) compared with the 2 in dual energy set-ups. This allows for a range of benefits, including better material decomposition [6], soft tissue contrast, and lower flux rates to be achieved for a given image quality [7].…”
Section: Introductionmentioning
confidence: 99%
“…We have in previous publications shown that decomposition into more than two basis materials is feasible in phantom studies with this detector [20,21]. This has also been demonstrated with other PCDs with phantoms [26][27][28][29][30][31], anatomical specimens [27,28,32], and animal models [33,34]. The purpose of this work is to provide proof of concept that unbiased three-material decomposition with iodine can be achieved in a clinical specimen with human tissue with an experimental photon-counting silicon detector in a bench-top setup.…”
Section: Introductionmentioning
confidence: 73%
“…Using a custom-made colon phantom filled with iodine and a gadolinium-filled capsule representing a contrast-enhanced polyp, Muenzel et al [34] demonstrated that differentiation between gadolinium-tagged polyps and iodine-tagged fecal material should be possible. Mixtures of iodine, gadolinium, and gold nanoparticles could be differentiated, as well [49]. The authors concluded that it might be possible to perform the imaging of multiple uptake phases in an organ with a single scan by injecting several contrast agents sequentially.…”
Section: Pre-clinical Evaluation Of Photon-counting Ctmentioning
confidence: 99%